PATH-12. IDENTIFYING MOLECULAR PROGNOSTIC MARKERS IN IDHwt GLIOBLASTOMA. (11th November 2019) - Alnahhas, Iyad; Giglio, Pierre; Gonzalez, Javier; Puduvalli, Vinay
Abstract: BACKGROUND: Despite our deeper understanding of the genomic alterations associated with glioblastoma (GBM), only a few genetic and epigenetic modifications have been proven to be meaningful in clinical practice. We have identified molecular parameters of prognostic relevance in IDHwt GBM using patient data from the Ohio State University (OSU) and the publicly available MSK-IMPACT database. METHODS: A clinically annotated database of glioma patients at OSU- whose tumors were analyzed through Foundation One genomic testing- was utilized to examine mutation and copy number variation (CNV) data. 73 patients with IDHwt GBM were included in this study cohort along with 200 similar patients from the MSK-IMPACT cohort. Data from the MSKCC group was extracted from the cBioPortal database. Altered genes were correlated with clinical outcomes using Cox proportional hazards models. Univariate and multivariate analyses were applied, and variables included: MDM/P53, CDKN2A/B, CDK/CCND, RB1, EGFR/ ERBB, FGFR, PDGFR/KIT, NF1, PI3K, PI3K class 2, MYC and TERT promoter mutations. RESULTS: Using univariate and multivariate analyses, EGFR activating alterations (amplification, mutations) and RB1 alterations (deletion, mutations) showed significant correlation with favorable outcome in IDHwt GBM: HR 0.496 for EGFR (p< 0.0001) and 0.454 for RB1 (p=0.025). Furthermore, the presence of PDGFR alterations, in EGFR altered tumors only, carried a significantly worse survival in univariate and multivariate analyses: HR 5.094 (p=0.004). This suggests an interaction between EGFR and PDGFR that could be of therapeutic relevance. CONCLUSIONS: We found that GBM tumors harboring EGFR and/or RB1 alterations have better survival compared to tumors that are EGFR/RB1 wild-type. Moreover, PDGFR alterations worsens survival in EGFR altered GBM. This data provides further insights that might guide targeted therapies in IDHwt GBM.